Conflitos, convergências e possibilidades de integração entre o estudo de impacto de vizinhança e o licenciamento ambiental municipal: estudos de caso em cidades médias paulistas - Abreu, Emanoele Lima (2023)
The Local Environmental Licensing (LEL) and the Neighborhood Impact Assessment (NIA) are instruments that aim at licensing activities in urban territory and represent an attempt to articulate urban and environmental problems, despite having legislation that derives from different concepts. This thesis researched the State of São Paulo, as it is growing in terms of the application of the LEL and NIA. This thesis aimed to advance the investigation of the relationship between urban and environmental regulation. We used qualitative research methods and resorted to three approaches. The first approach refers to bibliographic research, carried out through Systematic Literature Review (SLR). At SLR we investigate theoretical, conceptual and methodological approaches to LEL and NIA. In the second approach, we use multiple Case Studies, we seek to understand the application of these instruments in the four (04) cities and investigate the existence of an integrated urban environmental management in their territories. In the third, we interview stakeholders and public servants from the case study cities. Through the SLR, we found that the LEL and the NIA are instruments that need integration for urban environmental management in the country. However, there are still challenges of a technical, theoretical-conceptual and political-administrative nature that prevent this connection. In the Case Studies, three (03) cities studied did not have a specific law for NIA. In these cities, the Master Plan or the Land Use and Occupation Law are responsible for regulating NIA, with information complemented by terms of reference. Regarding the LEL, all cities had a specific law and, with the exception of Jundiaí, carried out environmental licensing through authorization by the state environmental agency. As for the interviews with stakeholders, we mapped the following related conflicts: the attribution of NIA and LEL instruments; the social agents involved; and the attribution of the state in the application of these instruments. Inserting the environmental dimension into local urban policies still faces political and institutional obstacles. The origin of these obstacles has deep roots in a series of conflicts of interest between different local social forces. Diagnosing, identifying and recognizing such conflicts is essential for the development of local urban-environmental governance.